Direct observation of hydrogen at defects in multicrystalline silicon. (7th August 2019) - Tweddle, David; Hamer, Phillip; Shen, Zhao; Markevich, Vladimir P.; Moody, Michael P.; Wilshaw, Peter R.
Abstract: Hydrogen passivation is a key industrial technique used to reduce the recombination activity of defects in multicrystalline silicon (mc‐Si). However, not all dislocations and grain boundaries respond well to traditional hydrogen passivation techniques. In order to understand the reasons for these different behaviours, and how superior passivation might be achieved, a method is required for the direct observation of hydrogen at these defects. Here, we present a novel characterisation technique based on a combination of transmission Kikuchi diffraction (TKD), atom probe tomography (APT), and isotopic substitution that enables unambiguous detection and quantification of hydrogen atoms present at crystallographic defects in mc‐Si. Abstract : In this paper, we combine hydrogen passivation, underpinned by isotopic substitution from an atomic source, with the 3D atomic‐scale characterisation technique atom probe tomography (APT), to present a novel experimental protocol for the direct and unambiguous imaging of individual hydrogen atoms at defects within crystalline silicon. This method allows for quantitative comparisons to be drawn regarding the difference in hydrogen content at different types of grain boundaries and between individual dislocations.